Konsep Fitrah dan Implikasinya Terhadap Pendidikan Anak Usia Dini (PAUD) - Nur Hasanah (IAIN TERNATE, 2022)
Islam recognizes that every human being who is born has been equipped with nature in the form of basic potential and abilities. These basic potentials are still hidden in him. The introduction of human nature will have implications for Islamic education. Islamic education exists to develop the human nature that it already has and minimize the development of human negative potential. The development of this nature is a must because these potentials are still in a simple form that is always waiting for the help and touch of others to develop it. Natural development must continue to be pursued through the educational process, considering the existence of human nature which is still weak (especially at the age of infancy). If there is no adult intervention, it is certain that the baby will be disabled and lose his humanity.